2012
DOI: 10.7727/wimj.2012.233
|View full text |Cite
|
Sign up to set email alerts
|

Marfan’s Syndrome: Pre-pubertal Aortic Rupture with Left Coronary Artery Aneurysms and Fistulas

Abstract: Aortic dissection and rupture occur in 20-40% of patients with Marfan's syndrome. This occurs predominantly in the third and fourth decade of life, contributing to the increased morbidity and mortality of this specific group of patients. This is the first known documented case report of prepubertal left coronary sinus rupture with left coronary artery aneurysms with fistulous communication to both the superior vena cava and right superior pulmonary vein, presenting with a continuous murmur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The major cardiovascular manifestation in Marfan syndrome is a progressive dilatation of the ascending aorta, leading to aortic aneurysm formation and, eventually, to fatal aortic rupture or dissection if there is no intervention. CAAs are rare but have been described in case reports (31,(101)(102)(103)(104). Becker and van Mantgem (103) performed an autopsy study of patients with Marfan syndrome and found histologic changes in the wall of the coronary arteries similar to changes noted in the aortic wall.…”
Section: Marfan Syndromementioning
confidence: 99%
“…The major cardiovascular manifestation in Marfan syndrome is a progressive dilatation of the ascending aorta, leading to aortic aneurysm formation and, eventually, to fatal aortic rupture or dissection if there is no intervention. CAAs are rare but have been described in case reports (31,(101)(102)(103)(104). Becker and van Mantgem (103) performed an autopsy study of patients with Marfan syndrome and found histologic changes in the wall of the coronary arteries similar to changes noted in the aortic wall.…”
Section: Marfan Syndromementioning
confidence: 99%
“…As far as CAFs association with genetic syndromes is concerned, CAFs have been sporadically described in an infant with 22q11 deletion syndrome [ 8 ] and a man with mosaic Klinefelter syndrome [ 9 ], as well as three older patients with clinical diagnoses of Marfan [ 10 ], Goldenhar [ 11 ], and Rendu-Osler-Weber [ 12 ] syndromes. The latter condition is associated with 5 different genetic causes, including ENG mutations at 9q34.11 [ 13 ], which is 9 Mb away from the critical Kleefstra region.…”
Section: Discussionmentioning
confidence: 99%
“…The infant with 22q11 deletion manifested left ventricular noncompaction and a CAF between the left coronary artery and the right ventricle outflow tract [ 8 ], whereas the man with Klinefelter syndrome had a CAF between the left coronary artery and the right ventricle [ 9 ]. The patient with Marfan syndrome had a left CAF draining into the superior vena cava and the right superior pulmonary vein, as well as a second fistulous communication between the left coronary sinus and both atria [ 10 ]. Marfan syndrome is associated with mutations or deletions in FBN1 at 15q21.1 [ 14 ], but the index patient did not have molecular confirmation of the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Treated with 0.7 mg/kg/day Carvedilol since his seventh month of life he never developed severe heart failure. However despite his good health status at the age of 9 years, a progressive aortic root dilatation and left conornary aneurysm [9] are still waiting for surgical repair. Perhaps this unique clinical course depends on the unique fibrillin-1 mutation, which has never been published before.…”
Section: Discussionmentioning
confidence: 99%